SUSTAINABLE DEVELOPMENT AS A PARADIGM FOR ENVIRONMENTAL CONSERVATION - Rusmanto, Rusmanto (Tahta Media Group, 2024)
This study aims to analyze the implementation of sustainable development principles as a paradigm for environmental conservation in Klaten Regency and to examine the roles of local government and community participation in supporting sustainable development. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, field observations, and analysis of regional policy documents, and were analyzed using thematic analysis involving data reduction, data display, and conclusion drawing. The findings indicate that the local government has integrated sustainable development principles into planning documents and environmental programs, such as community-based waste management and environmental rehabilitation initiatives. However, policy implementation still faces challenges, including limited cross-sectoral coordination, inconsistency in program execution, and the predominance of economic growth-oriented development. Meanwhile, community participation through environmental groups and local initiatives demonstrates significant potential for strengthening socially based sustainability. The study concludes that sustainable development in Klaten Regency requires strengthened collaborative governance, integrated cross-sector policies, and the internalization of sustainability values within regional development practices to ensure systematic and long-term environmental conservation.